2022
DOI: 10.54855/ijli.22114
|View full text |Cite
|
Sign up to set email alerts
|

Employing CLT Approach to Improve English Speaking Skill for Hau Giang Community College Students

Abstract: Teaching the English language to non-native students at Hau Giang community college is a concern for instructors. This research was conducted to examine whether the CLT approach is the effective teaching method that students expect. The research used survey questionnaires for teachers and students. The participants consisted of 16 teachers of English and 23 EFL students at Hau Giang community college. The quantitative data was collected through the Google form application. The finding indicates that necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, the findings in this research also corroborate that CLT facilitates the development of communicative competence by engaging students in the interactive and meaningful use of language, for example research conducted at Superior University and the University of Lahore found that both educators and learners believe that CLT is essential for academic and professional success, although its effectiveness is often hampered by outdated curricula and inadequate teacher training (Shahid et al, 2022). Similarly, a study at Hau Giang community college confirms that CLT creates a conducive communication environment, allowing students to interact and improve their language skills (Tran, 2022). In Malaysia, although communication strategies are widely used in job interviews, the high frequency of fillers indicates a lack of competence, suggesting that the implementation of CLT needs to be improved to be more effective (Awang et al, 2022).…”
Section: Differences Between Communicative Approach and Conventional ...mentioning
confidence: 99%
“…Furthermore, the findings in this research also corroborate that CLT facilitates the development of communicative competence by engaging students in the interactive and meaningful use of language, for example research conducted at Superior University and the University of Lahore found that both educators and learners believe that CLT is essential for academic and professional success, although its effectiveness is often hampered by outdated curricula and inadequate teacher training (Shahid et al, 2022). Similarly, a study at Hau Giang community college confirms that CLT creates a conducive communication environment, allowing students to interact and improve their language skills (Tran, 2022). In Malaysia, although communication strategies are widely used in job interviews, the high frequency of fillers indicates a lack of competence, suggesting that the implementation of CLT needs to be improved to be more effective (Awang et al, 2022).…”
Section: Differences Between Communicative Approach and Conventional ...mentioning
confidence: 99%
“…Those student-centered methods such as the content-based, task-based, project-based, to name a few can be traced back to the CLT approach. Consequently, the integration of listening, speaking, reading, and writing has also been advocated through the use of the CLT (Tran, 2022). The study, however, was limited to using the CLT in improving students' speaking skills.…”
Section: Integration Of Communicative Language Teaching Approach and ...mentioning
confidence: 99%
“…Thus, new research is required to close the knowledge gap. As learning to speak the English language has drawn much attention from educators and students, according to several literature and studies (Nguyen & Pham, 2022;Tran, 2022, Tuong, 2022, Vo, 2022, the researchers are motivated to investigate the implications of verbal learning style characteristics of college students' oral English skills.…”
Section: Introductionmentioning
confidence: 99%